تأثير اللغة الفارسية في تشكيل الهوية الإسلامية في الصين = The impact of Persian language on the formation of Islamic identity in China - Ahmad, Masitoh; Zhao, Dan (AL-HIKMAH RESEARCH AND PBLICATION CENTER, 2025)
ABSTRACT Persian has been the dominant language of culture and religion among Muslims in China for centuries. Historical evidence, including numerous Persian inscriptions on stones, abundant Persian manuscripts, and Chinese references to Persian, indicates a remarkable flourishing of this language in Chinese history. The use of Persian terms in the language of Chinese Muslims today is still strong evidence of the depth of this Persian influence. The problem of this research is to understand the role of Persian in shaping the Islamic identity of Chinese Muslims and its impact on religious culture and Islamic education during different historical periods, especially during the Mongol era and the Ming and Qing dynasties. This research seeks to explore the reasons for the flourishing and subsequent decline of Persian in China, focusing on its relationship with the cultural identity of Chinese Muslim society. This research relies on two approaches: the historical approach: to study the development of Persian arts and literature and their impact on Islamic society in China, it also relies on the analytical approach to analyze Persian literary and artistic texts produced in different periods. One of the most important results of the research is that Persian was a major tool in spreading Islam in China, as Muslim scholars used it to teach and interpret Islamic teachings.